Pengaruh Kepemimpinan, Stres Kerja Dan Konlik Kerja Terhadap Kinerja Karyawan (Studi Kasus Pada KUD Pakis) - Muhammad Ajye Saputra; Achmad Agus Priyono; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of leadership, work stress and work conflict on employee performance at KUD simultaneously or partially. This study uses quantitative research with a descriptive approach. The population in this study were KUD Pakis employees. The sampling technique used by the researcher is saturated sample or total sampling. Data analysis used multiple linear regression analysis which was processed with SPSS 25 software. The data collection method used was a questionnaire. The results showed that the variables of leadership, work stress and work conflict had a simultaneous effect on employee performance at KUD Pakis. The results of the study partially stated that the leadership variable had an effect on employee performance at KUD Pakis, the work stress variable had an effect on employee performance at KUD Pakis, and the work conflict variable had no effect on employee performance at KUD Pakis. Keywords : Leadership, Work Stress and Work Conflict on Employeed performance